AN EXPLORATION OF ETHNOMATHEMATICS IN TRADITIONAL LAYER CAKE FOOD - Dwi Masithoh N.K.S; Mei Lani Putri; Hepy Yista Adeliya; Susi Hermin Rusminati; Cholifah Tur Rosidah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Ethnomatematics is a process of learning mathematics that applies an approach to the culture that develops in society. Layer cake is a typical Indonesian food. This cake usually consists of two colors that are layered, so it is called a layer cake. This cake can be found in many areas in Indonesia, especially in traditional market traders and traditional snack cake shops. This layer cake is included in one of the legendary snacks and is one of the takjil menus. This study aims to describe the relationship between cultural heritage, namely layer cakes, and mathematics. This research method is ethnography. The data collection technique used in this research is by means of observation and documentation. This research is intended so that the Indonesian people and students can find out that this traditional Indonesian layer cake is related to learning mathematics. Learning mathematics related to this layer cake is the basic material for fractions which is learned in class II of elementary school.